2009
DOI: 10.1103/physrevlett.102.047001
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Quantum Spin-Gap State in the Static Stripe Phase of High-TemperatureLa2xSrxCuO4Superconductors

Abstract: Low-energy spin excitations were investigated in the static stripe phase of La2-xSrxCuO4 using elastic and inelastic neutron scattering on single crystals. For x=1/8 in which long-range static stripe order exists, an energy gap of E(g)=4 meV exists in the excitation spectrum in addition to strong quasielastic, incommensurate spin fluctuations associated with the static stripes. When x increases, the spectral weight of the spin fluctuations shifts from the quasielastic continuum to the excitation spectrum above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
66
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 44 publications
14
66
1
Order By: Relevance
“…On the other hand, this crystal is a good bulk superconductor with T c = 29 K, so it could be that there is a spin gap below T c in place of a SO-peak. 68 As one can see in Fig. 8, the SO-peak shifts to higher h with increasing x, reflecting a similar increase of δ as for the CO-peak; details will be discussed in Sec.…”
Section: Neutron Diffractionmentioning
confidence: 66%
See 1 more Smart Citation
“…On the other hand, this crystal is a good bulk superconductor with T c = 29 K, so it could be that there is a spin gap below T c in place of a SO-peak. 68 As one can see in Fig. 8, the SO-peak shifts to higher h with increasing x, reflecting a similar increase of δ as for the CO-peak; details will be discussed in Sec.…”
Section: Neutron Diffractionmentioning
confidence: 66%
“…As long as µSR detects static order, ND should as well, independent of a concomitant opening of a spin gap. 68 However, the weak CO-peak for x = 0.155 already suggests that any SO-peak will be extremely difficult to identify.…”
Section: Comparison With Lbco Nd-lsco and Eu-lscomentioning
confidence: 99%
“…17,19,21,[32][33][34] In Fig. 1(a), we show a constant energy scan obtained with the spectrometer set to energy transferhω = 0 meV.…”
Section: Resultsmentioning
confidence: 99%
“…The available experimental evidence is, however, limited and a consistent interpretation is lacking. A recent doping-dependent study of the low-energy dynamics in LSCO by M. Kofu et al 21 reported a correlation between the presence of incommensurate elastic magnetic scattering and gapless spin excitations near x max . These data were interpreted in terms of two components: a spin-gapped response similar to what is observed at optimal doping, 22 i.e., a gap caused by superconductivity, and a second component related to spin stripe-ordered or stripe-frozen domains.…”
Section: Introductionmentioning
confidence: 99%
“…For HTS, the parent, undoped, compounds are Mott insulators which display three dimensional (3D), commensurate (C) antiferromagnetic (AF) ground states 12,13 . This 3D C AF ground state is remarkably sensitive to the presence of mobile, doped holes, and less sensitive to the presence of doped mobile electrons 14 .…”
Section: Introductionmentioning
confidence: 99%